`PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK DALAM TEMA PEDULI TERHADAP MAKHLUK HIDUP - Rinci Simbolon; Hotma Tiolina Siregar (JURNAL TEMATIK, 2020)
This study aims to produce comic-based learning media. This type of research is development carried out through development which consists of research and research data, planning, product development, expert testing, field testing, and product improvement. The subjects of this study were 21 students. Feasibility is evidenced by the quality of the media made based on the order of material obtained by 4.25 or valid. Student response questionnaires were also conducted with the results obtained, namely 4.5 or very valid. The teacher response questionnaire obtained a score of 4.5 or very valid. Student responses to the simple comics that were developed were ≥ 60% of the 21 class IV respondent students to the 15 questionnaires. This means that the 15 questionnaires were responded positively by the students, while the response to the teacher's questionnaire was ≥ 60% of a respondent from SDN 14 Simbolon Purba to 12 questionnaires and responded positively by the teacher